Contractual Freedom and Corporate Governance in Britain in the Late Nineteenth and Early Twentieth Centuries. Issue 2 (2nd August 2017) - Guinnane, Timothy W.; Harris, Ron; Lamoreaux, Naomi R.
Abstract : British general incorporation law granted companies an extraordinary degree of contractual freedom. It provided companies with a default set of articles of association, but incorporators were free to reject any or all of the provisions and write their own rules instead. We study the uses to which incorporators put this flexibility by examining the articles of association filed by three random samples of companies from the late nineteenth and early twentieth centuries, as well as by a sample of companies whose securities traded publicly. Contrary to the literature, we find that most companies, regardless of size or whether their securities traded on the market, wrote articles that shifted power from shareholders to directors. We find, moreover, that there was little pressure from the government, shareholders, or the market to adopt more shareholder-friendly governance rules.